The investigation of vestibulary system in patients with thyroid dysfunctions - Ci̇gdem Firat Koca; Lezan Keski̇n; Mehmet Kelles; Turgut Celi̇k; Sukru Aydin; Seyma Yasar (Medicine Science)
A relationship has been detected among thyroid dysfunctions and vestibular pathologies. Our aim was to evaluate the vestibular system in cases with thyroid dysfunctions. Totally 71 patients between the ages of 20-50 with thyroid dysfunctions (35 hypothyroidic and 36 hyperthyroidic) and 36 participants with normal thyroid functions were included. Patients were also allocated as two groups based on antibody positivity. Pure tone audiometry and Vestibular Evoked Myogenic Potential tests were performed for all participants. In the left ear there was a numerically significance in the hypothyroids at 4000 and 8000 Hz (p=0.020 and p=0.014). In the right ear p13 and n23 latencies differed among the groups, (p=0.004 and p=0.001). The p13-n23 and n10-p15 amplitudes were decreased in both patient groups (p [Med-Science 2024; 13(4.000): 847-53]